Implementation and integration of high frequency messaging system with cryptographic features [compact disc] - 372087 Abd. Rahim Mat Sidek (Skudai : Universiti Teknologi Malaysia, 2006)
Thesis (Sarjana Kejuruteraan (Elektrik)) - Universiti Teknologi Malaysia, 2006